BENTUK-BENTUK DAN TAHAPAN KEARIFAN LOKAL PETANI DALAM KEGIATAN BUDIDAYA JAGUNG DI DESA MAROBEA KECAMATAN SAWERIGADI KABUPATEN MUNA BARAT - Hasrina, Waode; Rianse, Usman; Hamzah, Awaluddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The local wisdom of the community, which has existed since the ancestors of the Muna people passed down their knowledge from generation to generation, serves as a reminder of the importance of maintaining positive relationships with other humans, with nature, and with other creatures. This study aims to ascertain the forms and stages of farmers' local wisdom in corn cultivation activities in Marobea Village, Sawerigadi District, West Muna Regency. The informants were selected purposively based on their understanding of the focus of analysis, namely the local wisdom of the Marobea Village Community related to corn cultivation. The key informants were selected using the snowball sampling technique, or alternatively, according to the level of information saturation. Data were collected through observation, interviews, and document analysis with the assistance of an interview guide. The research is organized around two focal points: first, the form of textual and intangible local wisdom, and second, the stages of local wisdom of corn farmers in Marobea Village. The data analysis method employed is descriptive qualitative analysis, which is based on the Milles and Huberman model. This approach includes data reduction, data presentation, and conclusion drawing. The findings indicate that the form of farmers' local wisdom in maize cultivation in Mrobea Village is manifested in two distinct categories: tangible textual forms, encompassing procedures and value systems, and intangible forms, represented by prayers and mantras. The stages of corn cultivation in Marobea Village are associated with a set of local agricultural knowledge and practices. These include land preparation (detambori), seed provision (dewine), planting (detisa), maintenance (derawati), corn vegetable collection (depasele), and harvesting (detongka).